The Effect Of Emotional Intelligence On Performance Through Job Satisfaction And Job Stress Of Employees Of PT. BPR Buduran Deltapurnama Sidoarjo - Soetikno, Lie Djaja; Sutoyo; Zainuddin, Ahmad; Suminar, Lintang; Soleha, Siti Nur (Maksimal Jurnal : Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
The decline in the performance of PT. BPR Buduran Deltapurnama Sidoarjo in 2021-2023 shows that there are obstacles to employee productivity due to high target demands. This study aims to examine the influence of emotional intelligence on employee performance with job satisfaction and work stress as intervening variables, in employees of PT. BPR Buduran Deltapurnama Sidoarjo. The population in this study is 90 employees of PT BPR Buduran Deltapurnama Sidoarjo, with the number of samples in this study being 73 employees at PT. BPR Buduran Deltapurnama Sidoarjo. The test used in this study is Partial Least Squares (PLS).  The conclusions of this study are: Emotional intelligence can contribute to employee performance, Emotional intelligence can contribute to job satisfaction, Emotional intelligence can contribute to work stress, Job satisfaction is influential can contribute to employee performance, Work stress is influential in contributing to employee performance, Job satisfaction is a mediating variable in influencing the relationship between intelligence Emotional Impact on Employee Performance, Work Stress Becomes a Mediating Variable in Affecting the Relationship Between Emotional Intelligence and Employee Performance.